Perancangan Aplikasi Sistem Informasi Pendaftaran Siswa dengan Fitur Pemeriksaan Kelulusan dan Pengelolaan Kuota Berbasis Desktop - Fatimatus Zuhro; Dannisa Zahroh Amalia; Raka Izza Sabilillah; Muhammad Rizky Maulana; Nisa Dwi Septiyanti; Rizky Basatha (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2025)
The student admission process in many educational institutions is still conducted manually, leading to issues such as data duplication, input errors, and delays in reporting. This study designs and implements a desktop-based student registration information system using VB.NET and MySQL, equipped with an admission-status checking feature and an automated quota-management module. The system was developed using the waterfall model, consisting of requirement analysis, system design using UML, implementation, and black-box testing. Two user roles are supported: admin and student. Admin users can manage applicant data, configure program quotas, open or close the registration period, and generate reports, while student users can create accounts, complete registration forms, and independently check their admission results. The implementation results show that all core functions operate validly based on testing involving two respondents. The quota-management feature successfully restricts the number of applicants according to predetermined capacities, and the admission-status module automatically displays pass or fail results. The system improves administrative efficiency, enhances data accuracy, and reduces reliance on manual record-keeping. Therefore, this desktop application serves as an effective solution for schools requiring a reliable and efficient admission management system without depending on stable internet connectivity.